Magnetic Resonance Imaging-Based Morphometric Assessment of Sexual Dimorphism of Corpus Callosum - Amir Abdolmaleki; Reza Mastery Farahani; Seyed Kamran Ghoreishi; Fatemeh Shaerzadeh; Abbas Aliaghaei; Seyyed Hossein Mirjavadi; Hojjat-allah Abbaszadeh (Negah Institute for Scientific Communication, 2016)
Introduction: Interhemispheric transmission of signal is done by corpus callosum (CC) as the largest fiber tract in brain. CC comprised 5 segments of rostrum, genu, body, isthmus, and splenium. Contradictory reports exist about sexual dimorphism of CC. We designed this study to assess probable sexual differences of CC and its different parts in men and women. Methods: We analyzed magnetic resonance (MR) images of 68 females and 60 males in midsagittal view by PmsDViewer software. Data were analyzed by Student t test. These cases had no neurologic and pathologic diseases. Results: MRI anthropometric analysis indicates that all segments of CC are larger in men compared to women. Moreover, our results also revealed that although all segments of CC were bigger in men, this increase in size was more prominent in the anterior segments of CC. Conclusion: These findings indicate gender-related differences regarding CC segments. Notably, brain size as an interfering variable was eliminated in this study.